(untitled) (Terr@ Plural, 2021)
The State University of Ponta Grossa is a reference institution in Paleontology in Paraná, for being located on top of fossiliferous terrains of the Devonian and, mainly by the tradition in research in this area since 1969. In 2020, the Museum of Natural Sciences (MCN) was created on the UEPG campus with the proposal to enhance the scientific collections of regional and state geodiversity and biodiversity. Among the material on display in this space, there is a set of fossils representative of the Paraná paleontology with didactic potential and also for tourist visitation. The MCN has the support of research laboratories and their researchers to advance in the communication of science and, in the case of fossils, the Laboratory of Paleontology and Stratigraphy of the Department of Geosciences supports the curatorship and scientific investigation of the museum. The MCN concentrates on the most representative fossils of the region, culturally valuing the university collection and bringing to the public the results of decades of academic research, usually not accessible to the community. This paper presents the characteristics of this paleontological collection.